Reflections on a Decade of Using the Scholarship of Teaching and Learning - Randall E. Osborne, PhD; Paul Kriese, PhD; Heather Tobey (Park University, 2008)
This article explores lessons learned from a decade of teaching an online course on the politics and psychology of hatred using a scholarship of teaching and learning (SoTL) model. The authors illuminate course etiquette and a critical thinking model that incorporates SoTL into the ongoing fabric of the classroom. In addition, discussion centers on utilizing SoTL to satisfy colleagues concerned about "loss of content" in process oriented courses, and how to engage students in an ongoing, ever-changing, dialogue that can lead them to accept a more inclusive world view.